Pożądane cechy lidera według opinii zrzeszonych producentów rolnych województwa małopolskiego - Domagalska-Grędys, Marta (Desired Characteristics of a Leader in the Opinions of Agri-Producer Group Members of the Małopolska Region, 2006)
The figure of a leader has been the subject of many investigations each time evoking reflections on who it should be and what are his/her distinguishing features. Because of the mission a contemporary agri-producer group leader in the Małopolska region should fulfill, a survey was conducted among members (key informers) on the criteria of group leader selection and characteristics which the elect persons actually have. The results demonstrated only slight differences concerning the desired features in comparison with some earlier studies conducted in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 236-242